Novel robot-assisted minimally invasive surgical technique for the treatment of esophageal cancer - Michał Wiłkojć; Wojciech Migal; Agnieszka Majewska; Anna Różańska-Walędziak (Videosurgery and Other Miniinvasive Techniques)
A new trend toward the application robot-assisted minimally invasive esophagectomy (RAMIE) has started to develop in the field of gastrointestinal tract surgery. As compared with the current gold standard, minimally invasive esophagectomy, RAMIE facilitates more thorough upper mediastinal lymphadenectomy and reduces the risk of vessel damage. This study aimed to evaluate the technical feasibility and safety of RAMIE in patients with esophageal cancer based on the first 2 RAMIE procedures carried out in Poland. Both robotic procedures were successful, without the need for conversion to open surgery. There was no case of incomplete lesion removal or postoperative complications, indicating that RAMIE is a feasible and safe treatment option for patients with esophageal cancer and results in good postoperative recovery.